Isolation Of Extended-Spectrum B-Lactamase (ESBL) Producing Escherichia coli and Klebsiella pneumiae From Dr. Zainoel Abidin General Hospital, Aceh - Zinatul Hayati; Syamsul Rizal; Ridhia Putri (The International Journal of Tropical Veterinary and Biomedical Research, 2019)
Infection that occurs in Indonesia has increased more significantly than before, compared to the increasing bacterial multidrug resistance (MDR) as the cause of infection. A study conducted in 5 hospitals in Indonesia in 2013 showed that the prevalence rate of extended-spectrum β-lactamase (ESBL)-producing bacteria reached 32-68%. The objective of this study is to detect the prevalence and resistence pattern of ESBL-producing Escherichia coli and Klebsiella pneumoniae in Dr. Zainoel Abidin General Hospital, Banda Aceh. This study was conducted from 1 September 2016 to 31 December 2016. Specimen types included in this study were blood, sputum, urine, pus, mucosal swab, and another body fluids sample. The sampling method in this study was total sampling that is all clinical specimen examined in Clinical Microbiology Laboratory. Isolation and identification ESBL-producing bacteria was performed by VITEK-2 machine (Biomerieux). The result of this study is that a total 122 E. coli and K. pneumoniae were isolated. That consisted of 48 (39%) E. coli isolates and 74 (61%) K. pneumoniae isolates. From 48 E. coli isolates it was found out that 41 (85%) had ESBL phenotypes and from 74 K. pneumoniae isolates it was found out that 59 (80%) had ESBL phenotypes. In total, 100 (82%) isolates from 122 isolates had ESBL phenotypes. Distribution of ESBL-producing E. coli and K. pneumoniae based on sample was 24 (89%) isolates from the total of 27 urine isolates, 18 (95%) isolates from the total of 19 blood isolates, 28 (78%) isolates from the total of 36 sputum isolates, and 30 (75%) isolates from the total of 40 pus isolates. Antibiotic sensitivity pattern of the E. coli and K. pneumoniae isolates had high sensitivity to amycasin dan meropenem which was above 89%. Meanwhile, it also had sensitivity to Fosfomycin and Piperacyclin-Tazobactam by 80% and 77% respectively. Another antibiotic was less effective